Black Walnut (Juglans nigra) Extracts Inhibit Proinflammatory Cytokine Production From Lipopolysaccharide-Stimulated Human Promonocytic Cell Line U-937 - Ho, Khanh-Van; Schreiber, Kathy L.; Vu, Danh C.; Rottinghaus, Susan M.; Jackson, Daniel E.; Brown, Charles R.; Lei, Zhentian; Sumner, Lloyd W.; Coggeshall, Mark V.; Lin, Chung-Ho (Frontiers in Pharmacology, 2019)
Black walnut (Juglans nigra L.) is an excellent source of health-promoting compounds. Consumption of black walnuts has been linked to many health benefits (e.g., anti-inflammatory) stemming from its phytochemical composition and medicinal properties, but these effects have not been systematically studied or characterized. In this study, potential anti-inflammatory compounds found in kernel extracts of ten black walnut cultivars were putatively identified using a metabolomics profiling analysis, revealing differences in potential anti-inflammatory capacities among examined cultivars. Five cultivars were examined for activities in the human pro-monocytic cell line U-937 by evaluating the effects of the extracts on the expression of 6 human inflammatory cytokines/chemokines using a bead-based, flow cytometric multiplex assay. The methanolic extracts of these cultivars were added at four concentrations (0.1, 0.3, 1, and 10 mg/mL) either before and after the addition of lipopolysaccharide (LPS) to human U-937 cells to examine their effect on cytokine production. Results from cytotoxicity and viability assays revealed that the kernel extracts had no toxic effect on the U-937 cells. Of the 13 cytokines (IL-1β, TNF-α, MCP-1, IL-6, IL-8, IL-10, IL-12, IL-17, IL-18, IL-23, IL-33, IFN-α, IFN-γ) measured, only 6 were detected under the culture conditions. The production of the six detected cytokines by PMA-differentiated, LPS-stimulated U-937 was significantly inhibited by the kernel extracts from two cultivars Surprise and Sparrow when the extracts were added prior to the addition of LPS. Other cultivars (Daniel, Mystry, and Sparks) showed weak or no significant effects on cytokine production. In contrast, no inhibitory effect was observed on the production of cytokines by PMA-differentiated, LPS-stimulated U-937 when the kernel extracts were added after the addition of LPS. The findings suggest that the extracts from certain black walnut cultivars, such as Sparrow and Surprise, are promising biologic candidates for potentially decreasing the severity of inflammatory disease.